Acquisition risk in the purchase of properties by a real estate investment trust fund manager / Muhamad Hafiz Jantan - Jantan, Muhamad Hafiz (2012)
The purpose of this applied research is primarily to help the management to formulate strategies and program to overcome the turnover problem among ABC Berhad and its subsidiary, as well as to ensure efficiency, effectiveness, high productivity and profitability in the company. Hence, the research will try to identify whether the acquisition risk in the purchase of property by a real estate investment trust fund manager such as at ABC Berhad. Using data collected from company records and interviews, this research investigates questions such as: what is the basis of properties acquisition practised by Subsidiary A and ABC Berhad. Is there a possibility of collusion happening between some staff of Subsidiary A or ABC Berhad with sellers or agents of properties for fraudulent purposes in the property acquisition process? Is there a problem with rental default in the properties managed by ABC Berhad and its subsidiaries? Is there a problem with decisions made regarding bad purchase of property? This research further highlights the importance of information on risk acquisition especially as properties and managing rental requires awareness of the way in which information systems work. The research findings here will show the main reasons how poor management may impact bad decisions on property acquisition and cause negative effects on collection of rental. In order to solve these issues, the researcher has come up with some recommendations that are applicable for the company to resolve their problems.